Advancing global herbal medicine: Enhancing herb quality through innovative strategies explored in Hong Kong - An international hub - Ngai, Hiu-Lam; Shaw, Pang-Chui (Phytomedicine Plus : International journal of phytotherapy and phytopharmacology, 2025)
The Hong Kong Department of Health has been inspecting numerous medicinal herbs circulating in the market every year. Herbs have been identified recurrently to have problems such as over-limit aflatoxins and toxic alkaloids, and the distributors had to recall the problematic herbs. Despite the negative business consequences, the problems persisted. This study identified the contributors to such a phenomenon, particularly the reasons for unchanging supply chain practices in Hong Kong. We interviewed 16 stakeholders from the Chinese herbal medicine industry to investigate the reasons behind sub-optimal supply chain practices. The interviews were analysed using a coding framework developed by Pisani and colleagues in 2019 to analyse national risks for medicines of sub-optimal quality. The survey's purpose was to identify risks in market dynamics and policies associated with sub-standard and adulterated medicinal herbs in Hong Kong. Problems with herbs’ quality in Hong Kong are attributed to harvesting, collecting, processing and packaging errors as well as storage errors. Furthermore, batch differences contributed to quality issues. The results revealed the lack of expertise and motivation in the Chinese medicine industry in terms of self-surveillance and the eradication of such errors. Moreover, it was found that chemical inspection tests were generally avoided due to cost and time concerns. The current situation is not conducive to consumer rights and public health protection, and supply chain practices should be improved to provide high-quality herbs to the community consistently. We propose establishing a centralised system to purchase herbs. A track-and-trace electronic system can be set up for efficient tracing of the sources and time of transactions such as herb purchase and dispensing. A registration system of Chinese pharmacists is recommended to ensure professionalism and regulatory responsibility, protect the quality of prescriptions, ensure the safe use of herbs and protect public health. These strategies can facilitate the internationalisation of Hong Kong herbs by achieving high standards of quality. Since Hong Kong is an international city, the implementation of the strategies in this proposal can serve as a demonstration of ways to improve the quality of herbs on a global scale.